2013
DOI: 10.1111/jzo.12090
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetics and wing morphometrics show a lack of structuring across island and coastal populations of the drone fly in theMediterranean

Abstract: The Mediterranean basin is a region of species richness, rarity and endemism, and is thus an area of significant conservation importance. Conservation of insect biodiversity benefits pollination services in the fragmented Mediterranean landscape. However, the question of the distribution patterns of an important longdistance pollen disperser, the hoverfly Eristalis tenax (Diptera, Syrphidae), remains open. Therefore, we explored the spatial distribution of genetic and phenotypic diversity of this species acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 90 publications
2
7
0
Order By: Relevance
“…We obtained individual genotypes from subsets of individuals used in previous studies: Francuski et al . (2011; 2013 a,b ; 2014 a,b ). Sample sizes in populations ranged from 11 to 122 individuals while distance between sampling sites ranged from 17 to 3322 km.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained individual genotypes from subsets of individuals used in previous studies: Francuski et al . (2011; 2013 a,b ; 2014 a,b ). Sample sizes in populations ranged from 11 to 122 individuals while distance between sampling sites ranged from 17 to 3322 km.…”
Section: Methodsmentioning
confidence: 99%
“…Up to date, two studies were brought to bear on questions of E. tenax widerange movement and gave contrasting results. Using genetic (allozymes and mitochondrial DNA sequences of the cytochrome c oxidase subunit I gene) and phenotypic data (wing shape), our previous study suggested that E. tenax populations in the Central-Eastern Mediterranean are largely connected and that there is an absence of geographic structuring across island and coastal populations (Francuski et al, 2014b). On the other hand, application of landscape genetics revealed a subtle but significant subdivision between Balkan populations and populations from Central and Northern Europe of the taxon despite the continuous between-population exchange of individuals across the European landmass (Francuski et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Such consistent allometric patterns, accompanied with the conserved pattern of SShD (e.g. Francuski et al, 2011; Francuski, Djurakic, Ludoški, et al, 2014; Francuski, Djurakic, Ståhls, & Milankov, 2014; Ludoški et al, 2008; Milankov et al, 2010a, 2010b, 2013), might be developmentally (Bolstad et al, 2015; Reis et al, 2021) and/or evolutionarily constrained, suggesting species‐specific adaptations and plastic responses. For instance, the percentage of wing shape variation explained by allometry was found to range from 34% ( Drosophila melanogaster ) to 16% ( Ceratitis capitata ) and 13% ( Musca domestica ), which was congruent with species‐specific scaling relationships (Reis et al, 2021).…”
Section: Discussionmentioning
confidence: 71%
“…Contrary to this, deeper insights into spatial pattern of genetic and phenotypic variation on the local and regional scale were provided. Indeed, landscape genetic studies suggested that populations of this highly migratory species were largely connected (Francuski, Djurakic, et al, 2013; Francuski, Djurakic, Ståhls, & Milankov, 2014; Francuski, Ludoški, & Milankov, 2013; Francuski & Milankov, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To address these important knowledge gaps, in this study, we generated both molecular and morphological data for the same individuals, resulting in two parallel but independent data sets. Surprisingly, few studies have adopted this approach despite the clear potential value thereof (but see Bouyer et al 2007;Francoy et al 2009;Bomfim et al 2011;Krosch et al 2013;Francuski et al 2014;Schutze et al 2015a,b).…”
Section: Introductionmentioning
confidence: 99%